Hours of recreation, vol. II A collection of transcriptions for Violine (I and II), cello and piano - SINNHOLD, Rudolf (J. Fischer & Bro., 1904)
Ave VerumnBelieve me, if all those endearing young charmsnDainty butterflynGavotte CharacteristiquenHosannanOld black JoenRecollection of the dancenSinfonia RusticananSounds from AidanSounds from ParsifalnTwo favorite Hymn Tunes